Activation of a child’s subjectivity in the upbringing space of free self-determination on the basis of pedagogy of freedom - Alla Rastrygina (Problemy Wczesnej Edukacji)
The article updates the problem of reconstruction of the modern upbringing process, the leading idea of which is the targeting of its goals, content, forms and methods at self-development of a child and the becoming of a child’s subjectivity as an active, purposeful, initiative, creative and constructive position in his or her own livelihoods on the basis of humanistic values of a democratic society. The conceptual provisions of the author’s concept of freedom pedagogy have become the starting point in solving the mentioned problem.